The Influence of Local Government Information Systems, Human Resources, Organizational Commitment on the Quality of Financial Reports - Ika Rahmawati; Sri Rahayu; Muhammad Gowon (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This research aims to determine the influence of the implementation of regional government information systems, human resource competence, organizational commitment, and internal control on the quality of financial reports. The study employs a quantitative method using multiple linear regression analysis. Primary data were collected through questionnaires distributed to respondents, and data were processed using SPSS version 27. The findings reveal that human resource competence and organizational commitment have a significant positive effect on the quality of financial reports. In contrast, the implementation of regional government information systems and internal control do not show a significant effect. These results indicate that improving the quality of financial reports in regional governments is more dependent on the quality of human resources and the level of organizational commitment rather than the sole reliance on information systems or internal control mechanisms. The study provides insights for policymakers to prioritize competence development and foster a culture of organizational accountability to enhance financial reporting outcomes.